Ideias históricas sobre a construção de Goiânia: projeto de ensino para o 5º ano do ensino fundamental na perspectiva da educação histórica - Fleury, Eunice Aparecida Antunes (2021)
This research has as main focus the work with Local History, more specifically, the History of the construction of Goiania between the 1930s and 1940s, from the scientific domain of Historical Education. The area of investigation of historical education has as tradition the dialogue between the science of history and the practice of teaching and understands praxis as a determining factor of science. Thus, it is a field of investigation that, in trying to understand how students think and reason historically and how they develop historical consciousness, seeks elements to draw a proper design of the didactics of history. It is in this sense of approaching practice with science and trying to collaborate with the field of research of Historical Education that this research is situated. As an initial assumption that motivated the idea of research and the elaboration of the educational product, it was suspected that there are few materials on the theme of Goiania's History specific to the last years of elementary school. Then, a quantitative research was done with history teachers of the Goiania Municipal network, to corroborate or not such an idea. As an Educational Product, entitle “History of the construction of Goiânia: investigations and discoveries for the 5th year of elementary school”, a teaching project was created with a set of historical cognition activities for students and explanatory material for the teacher. This material was applied in two classes E of two schools of the Goiania Municipal Education Network. The data collected in the participant observation research and the answers of the historical cognition activities will be used as base elements for the investigation if this material contributed with the historical learning, for the elaboration of the historical time concept and if it collaborated with the development of the historical consciousness of the students.